Improved safety of lithium secondary batteries

A multi-layered electrode structure with carbon and silicon-based materials in the negative electrode, and lithium composite metal oxides with phosphoric acid iron compounds in the positive electrode, addresses the safety issues of lithium nickel metal oxides by minimizing heat generation and enhancing stability in lithium secondary batteries.

JP2025503650AActive Publication Date: 2025-02-04LG ENERGY SOLUTION LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2024541240
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-07-21
Filing Date
2023-07-17
Publication Date
2025-02-04
Estimated Expiration
2043-07-17

AI Technical Summary

Technical Problem

Lithium nickel metal oxides used in secondary batteries exhibit high energy density but have low chemical and structural stability, leading to rapid heat generation and potential ignition or explosion due to internal short circuits, especially in medium-sized devices like electric vehicles and power storage systems.

Method used

A multi-layered negative electrode structure incorporating carbon-based and silicon-based active materials, along with a layered positive electrode using lithium composite metal oxides and phosphoric acid iron compounds, is designed to reduce heat generation and enhance safety by minimizing current flow during internal short circuits.

Benefits of technology

The proposed electrode structure improves safety and maintains high energy density by reducing heat generation and preventing rapid temperature rises during internal short circuits, enhancing the stability of lithium secondary batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025503650000001_ABST
    Figure 2025503650000001_ABST
Patent Text Reader

Abstract

The present invention relates to a negative electrode for a lithium secondary battery and a lithium secondary battery including the same. The negative electrode for a lithium secondary battery has the following advantages: i) it contains a silicon-based material as a negative electrode active material and has high energy density; and ii) it has an individual composite layer made of a silicon-based material having relatively low electrical conductivity at the outermost shell of a multi-layered negative electrode composite layer, thereby reducing the amount of current and the amount of heat generated when an internal short circuit occurs, thereby improving safety of the secondary battery against internal short circuit.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a lithium secondary battery with improved safety against internal short circuits.

[0002] This application claims the benefit of priority based on Korean Patent Application No. 10-2022-0090334 filed on July 21, 2022, and all contents disclosed in the document of the Korean patent application are included as part of this specification.

Background Art

[0003] In recent years, lithium secondary batteries have been widely applied not only to small devices such as portable electronic devices but also to medium and large-sized devices such as battery packs or power storage devices for hybrid vehicles and electric vehicles.

[0004] In order to apply such a secondary battery to medium and large-sized devices, a high energy density is required. Therefore, a ternary compound containing nickel (Ni), cobalt (Co), manganese (Mn), etc., specifically, LiNi with a nickel (Ni) content of 60% or more a Co b Mn c O2 (0.6 < a ≦ 0.9, a + b + c = 1), a layered lithium nickel metal oxide is used as a positive electrode active material to realize high capacity. However, lithium nickel metal oxide shows low chemical and structural stability although the capacity increases as the nickel (Ni) content increases, so a heat generation reaction easily occurs. In particular, in the case of lithium nickel metal oxide, the heat generation onset point is low, and once the heat generation reaction starts, it can rapidly increase the temperature inside the battery and induce ignition or explosion, so there is a problem of low safety.

[0005] The exothermic reaction of the positive electrode active material may be induced when a short circuit current flows inside the battery, i.e., when an internal short circuit occurs. More specifically, the short circuit current may occur mainly when a short circuit occurs inside the secondary battery due to the penetration of a needle-like object, or when a short circuit occurs in an electronic device connected to the secondary battery. In addition, when a short circuit occurs in a lithium secondary battery, a rapid electrochemical reaction occurs at the positive and negative electrodes, generating heat. The generated heat is conducted to the surrounding materials, and the temperature of the secondary battery cell rises at a high rate due to this thermal conduction, resulting in the cell ignition. In particular, in the case of a battery pack including a number of lithium secondary battery cells, heat generated in any one cell is transmitted to the surrounding cells and affects the other cells, resulting in the battery pack ignition.

[0006] Therefore, there is a demand for the development of a battery that exhibits high energy density while improving safety issues caused by internal short circuits. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] Korean Patent Publication No. 10-2020-0024980 [Patent Document 2] Korean Patent Publication No. 10-2017-0004253 Summary of the Invention [Problem to be solved by the invention]

[0008] SUMMARY OF THE PRESENT DISCLOSURE ... An object of the present invention is to provide a negative electrode which has high energy density and which improves safety issues caused by internal short circuits, a lithium secondary battery including the same, and a secondary battery module including the same. [Means for solving the problem]

[0009] To solve the above-mentioned problems, In one embodiment, the present invention comprises: A first negative electrode mixture layer or an nth negative electrode mixture layer (n≧2) is disposed on a negative electrode current collector; the first negative electrode mixture layer or the (n-1)th negative electrode mixture layer includes a first negative electrode active material containing a carbon-based material and a second negative electrode active material containing a silicon-based material; The nth negative electrode mixture layer provides a negative electrode for a lithium secondary battery, comprising a second negative electrode active material containing a silicon-based material.

[0010] In this case, the first negative electrode composite layer or the n-1th negative electrode composite layer may have an increased content or a content ratio of the second negative electrode active material as the position of the individual negative electrode composite layer changes from the first negative electrode composite layer to the n-1th negative electrode composite layer.

[0011] In addition, the carbon-based material of the first negative electrode active material may include one or more selected from the group consisting of soft carbon, hard carbon, natural graphite, artificial graphite, expanded graphite, non-graphitizable carbon, carbon black, acetylene black, ketjen black, carbon nanotubes, fullerene, activated carbon, graphene, and carbon fiber.

[0012] The silicon-based material of the second negative electrode active material is silicon (Si), silicon carbide (SiC), and silicon oxide (SiO q , where 0.8≦q≦2.5) may be included.

[0013] The second negative electrode active material may be included in an amount of 1 to 20% by weight based on the total weight of the negative electrode active material.

[0014] In addition, the second negative electrode active material may have a spheroidization degree of 0.5 to 1.0, and the spheroidization degree may decrease as the position of the individual negative electrode mixture layer changes from the first negative electrode mixture layer to the nth negative electrode mixture layer.

[0015] The negative electrode mixture layers may have a total thickness of 50 μm to 300 μm, and the thickness of the nth negative electrode mixture layer may be 5% to 30% of the total thickness of the positive electrode mixture layers.

[0016] In one embodiment, the present invention further comprises: There is provided a lithium secondary battery including the above-described anode according to the present invention, a cathode, and a separator disposed between the anode and the cathode.

[0017] In this case, the positive electrode may have a first positive electrode composite layer or an mth positive electrode composite layer (where m≧2) disposed on a positive electrode current collector, and the first positive electrode composite layer or the mth positive electrode composite layer may include a first positive electrode active material including a lithium composite metal oxide represented by Chemical Formula 1, and a second positive electrode active material including an iron phosphate compound represented by the following Chemical Formula 2.

[0018] [Chemical formula 1] Li x [Ni y Co z Mn w M 1 v ]O2

[0019] [Chemical formula 2] Life a M 2 1-a XO4

[0020] In the above Chemical Formula 1 and Chemical Formula 2, M 1 is one or more elements selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B and Mo, x, y, z, w, and v are in the range of 1.0≦x≦1.30, 0.1≦y<1, 0≦z≦1, 0≦w≦1, 0≦v≦0.1, and y+z+w+v=1, M 2 is one or more elements selected from the group consisting of W, Cu, Fe, V, Cr, CO, Ni, Mn, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B and Mo; X is one or more selected from the group consisting of P, Si, S, As and Sb; a is 0≦a≦0.5.

[0021] In addition, the content or the proportion of the content of the second positive electrode active material in each positive electrode mixture layer may increase as the position of the individual positive electrode mixture layer changes from the first positive electrode mixture layer to the mth positive electrode mixture layer.

[0022] The second positive electrode active material may be contained in an amount of less than 10% by weight based on the total weight of the positive electrode mixture layer.

[0023] The positive electrode mixture layer may have a total thickness of 50 μm to 300 μm.

[0024] Further, in one embodiment, the present invention provides There is provided a secondary battery module including the lithium secondary battery according to the present invention. Effect of the Invention

[0025] The negative electrode for a lithium secondary battery according to the present invention contains a silicon-based material as a negative electrode active material and has a high energy density. Since the outermost shell of a multi-layered negative electrode composite layer includes an individual composite layer made of a silicon-based material having a relatively low electrical conductivity, the amount of current generated when an internal short circuit occurs can be reduced, thereby improving the safety of the secondary battery against an internal short circuit. [Brief description of the drawings]

[0026] [Figure 1] 1 is a cross-sectional view showing a structure of a negative electrode for a lithium secondary battery according to the present invention. [Diagram 2] 1 is a cross-sectional view showing the structure of a lithium secondary battery including a negative electrode according to the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0027] Since the present invention can be modified in various ways and can have various embodiments, specific embodiments are described in detail in the detailed description.

[0028] However, this is not intended to limit the invention to the particular embodiments, but should be understood to include all modifications, equivalents, or alternatives falling within the spirit and scope of the invention.

[0029] In the present invention, the terms "comprise" and "have" are intended to specify the presence of features, numbers, steps, operations, components, parts, or combinations thereof described in the specification, but should be understood as not precluding the presence or additional possibility of one or more other features, numbers, steps, operations, components, parts, or combinations thereof.

[0030] In addition, in the present invention, when a layer, film, region, plate, or other portion is described as being "on" another portion, this includes not only the case where it is "directly on" the other portion, but also the case where there is another portion in between. Conversely, when a layer, film, region, plate, or other portion is described as being "under" the other portion, this includes not only the case where it is "directly under" the other portion, but also the case where there is another portion in between. In addition, in the present application, being "on" can include not only the case where it is located at the top, but also the case where it is located at the bottom.

[0031] The present invention will now be described in more detail.

[0032] <Negative electrodes for lithium secondary batteries> In one embodiment, the present invention comprises: A first negative electrode mixture layer or an nth negative electrode mixture layer (n≧2) is disposed on a negative electrode current collector; the first negative electrode mixture layer or the (n-1)th negative electrode mixture layer includes a first negative electrode active material containing a carbon-based material and a second negative electrode active material containing a silicon-based material; The nth negative electrode mixture layer provides a negative electrode for a lithium secondary battery, comprising a second negative electrode active material containing a silicon-based material.

[0033] The negative electrode for a lithium secondary battery according to the present invention includes a negative electrode mixture layer produced by applying a slurry containing a negative electrode active material onto a negative electrode current collector, followed by drying and pressing. The slurry may further selectively contain a conductive material, a binder, other additives, and the like, as necessary.

[0034] Here, the negative electrode includes a negative electrode current collector, and a negative electrode composite material layer having a multilayer structure in which two or more individual composite material layers are laminated on the negative electrode current collector.

[0035] 1, the negative electrode composite material layer has a structure in which n (n≧2) individual negative electrode composite layers 121 are laminated on the negative electrode current collector 11. At this time, the negative electrode composite material layer laminated on the surface in contact with the negative electrode current collector 11 is a first negative electrode composite material layer 121a, and a second negative electrode composite material layer or an nth negative electrode composite material layer 121n is sequentially laminated on the first negative electrode composite material layer 121a, so that n individual negative electrode composite material layers 121 are located on the negative electrode current collector 11.

[0036] The number of layers of the negative electrode mixture layer is not particularly limited as long as it has a structure of two or more layers (n≧2), and specifically may be 2 to 10 layers, 2 to 8 layers, 2 to 6 layers, or 2 to 4 layers. By adjusting the number of layers of the negative electrode mixture layer within the above range, the present invention can easily adjust the internal composition of the negative electrode mixture layer depending on the position, for example, the composition of the negative electrode mixture layer relatively adjacent to the positive electrode, while preventing a decrease in the manufacturing efficiency of the negative electrode.

[0037] In addition, the negative electrode mixture layer may use a negative electrode active material commonly used in the art, and preferably may include both a first negative electrode active material containing a carbon-based material and a second negative electrode active material containing a silicon-based material.

[0038] Specifically, the first negative electrode active material may be composed of a carbon-based material mainly composed of carbon (C). Such carbon-based materials may include at least one of graphite having a completely layered crystal structure like natural graphite, soft carbon having a low-crystalline layered crystal structure (graphene structure; a structure in which planes of a hexagonal honeycomb pattern of carbon are arranged in layers), and hard carbon having these structures mixed with non-crystalline parts, artificial graphite, expanded graphite, non-graphitizable carbon, carbon black, acetylene black, ketjen black, carbon nanotubes, fullerene, activated carbon, graphene, and carbon fiber.

[0039] The second negative electrode active material may be composed of a silicon-based material mainly composed of silicon (Si). The silicon-based material may include at least one of silicon (Si), silicon carbide (SiC), silicon monoxide (SiO), and silicon dioxide (SiO2). Here, when silicon monoxide (SiO) and silicon dioxide (SiO2) are uniformly mixed or composited and included in the negative electrode composite layer, the silicon-based material is called silicon oxide (SiO q , where 0.8≦q≦2.5).

[0040] In addition, the total negative electrode active material including both the first negative electrode active material and the second negative electrode active material may be included in an amount of 90 to 99 wt %, specifically 92 to 98 wt %, or 95 to 99 wt %, based on the total weight of the negative electrode mixture layer.

[0041] In addition, the second negative electrode active material may be included in an amount of 1 to 20 wt % based on the total weight of the negative electrode active material, specifically, 1 to 9 wt %, 3 to 7 wt %, 5 to 15 wt %, 11 to 19 wt %, or 13 to 17 wt % based on the total weight of the negative electrode active material. By adjusting the content of the second negative electrode active material within the above range, the present invention can minimize the volume change rate of the battery due to charging and discharging, and at the same time, can improve the charging capacity per unit mass while reducing the amount of lithium consumption and irreversible capacity loss during the initial charging and discharging of the battery.

[0042] In addition, the first negative electrode active material and the second negative electrode active material are all included in the n-1 negative electrode composite layers, and as the position of the individual negative electrode composite layer changes from the first negative electrode composite layer in contact with the negative electrode current collector to the n-1th negative electrode composite layer farthest from the negative electrode current collector, the content of the second negative electrode active material included in the individual negative electrode composite layer or the ratio of the content of the second negative electrode active material to the weight of the individual negative electrode composite layer may increase.

[0043] As an example, the second negative electrode active material may be contained in the first negative electrode mixture layer at 1 to 45 wt % based on the total weight of the second negative electrode active material, and may be contained in the second negative electrode mixture layer at 55 to 99 wt % based on the total weight.

[0044] As another example, the second negative electrode active material may be contained in the first negative electrode mixture layer at 1 to 10 wt % based on the total weight of the second negative electrode active material, in the second negative electrode mixture layer at 10 to 40 wt % based on the total weight, and in the third negative electrode mixture layer at 40 to 89 wt % based on the total weight.

[0045] As another example, the second negative electrode active material may be contained in the first negative electrode mixture layer at 1 to 5 wt % based on the total weight of the second negative electrode active material, in the second negative electrode mixture layer at 5 to 15 wt % based on the total weight, in the third negative electrode mixture layer at 15 to 30 wt % based on the total weight, and in the fourth negative electrode mixture layer at 30 to 79 wt % based on the total weight.

[0046] The first negative electrode active material contains a carbon-based material, and therefore exhibits excellent electrical properties such as electrical conductivity. However, when a short circuit current flows inside the secondary battery, for example, when a short circuit occurs inside the secondary battery due to penetration of a needle-like object, the carbon-based material with high electrical conductivity increases the amount of short circuit current between the positive electrode and the negative electrode. As a result, short circuit heat is significantly generated inside the secondary battery, which may accelerate the heat generation reaction of the secondary battery. However, the present invention i) includes an individual composite layer composed of a second negative electrode active material containing a silicon-based material as the outermost layer of the negative electrode composite layer, i.e., the nth negative electrode composite layer, and at the same time ii) increases the concentration of the second negative electrode active material containing a silicon-based material having a relatively lower electrical conductivity than the carbon-based material from the innermost to the outermost of the negative electrode composite layer, i.e., from the first negative electrode composite layer to the n-1th negative electrode composite layer, thereby reducing the amount of short circuit current during an internal short circuit in the secondary battery. This has the advantage of reducing and / or delaying heat generation in the secondary battery.

[0047] In addition, the second negative electrode active material may show a tendency that the sphericity of the active material decreases from the first negative electrode composite layer to the nth negative electrode composite layer. Here, the "sphericity" may mean the ratio of the shortest diameter (minor axis) to the longest diameter (major axis) among any diameters passing through the center of the particle, and when the sphericity is 1, it means that the particle shape is spherical. The sphericity may be measured using a particle shape analyzer.

[0048] Specifically, the second negative electrode active material may have a sphericity of 0.5 to 1.0, and the sphericity may decrease from the first negative electrode mixture layer to the nth negative electrode mixture layer, so that the second negative electrode active material may have a constant sphericity gradient.

[0049] As one example, the second negative electrode active material included in the first negative electrode mixture layer may have a sphericity of 0.8 to 1.0, and the second negative electrode active material included in the second negative electrode mixture layer may have a sphericity of 0.5 to 0.7.

[0050] As another example, the second negative electrode active material included in the first negative electrode composite layer may have a sphericity of 0.9 to 1.0, the second negative electrode active material included in the second negative electrode composite layer may have a sphericity of 0.7 to 0.8, and the second negative electrode active material included in the third negative electrode composite layer may have a sphericity of 0.5 to 0.6.

[0051] The present invention can reduce the electrical conductivity at the surface of the negative electrode mixture layer in contact with the separator without reducing the energy density of the negative electrode mixture layer by controlling the sphericity of the second negative electrode active material to have a constant gradient depending on the position of the negative electrode mixture layer including the second negative electrode active material.

[0052] Furthermore, the total thickness of the negative electrode composite layer is not particularly limited, but may be specifically 50 μm to 300 μm, more specifically 100 μm to 200 μm, 80 μm to 150 μm, 120 μm to 170 μm, 150 μm to 300 μm, 200 μm to 300 μm, or 150 μm to 190 μm.

[0053] In addition, the thickness of the nth negative electrode mixture layer located at the outermost layer and in contact with the separator among the individual negative electrode mixture layers constituting the negative electrode mixture layer may be adjusted to a certain range. Specifically, the thickness of the nth negative electrode mixture layer may be 5% to 30% of the total thickness of the negative electrode mixture layers, more specifically, 5% to 20%, 5% to 15%, 5% to 10%, or 10% to 15% of the total thickness of the negative electrode mixture layers.

[0054] In the present invention, the total thickness and individual thicknesses of the negative electrode composite layers are adjusted to fall within the above ranges, so that the electrical conductivity at the surface of the negative electrode can be reduced during normal operation of the secondary battery. As a result, the negative electrode of the present invention can not only prevent a reduction in the energy density of the electrode, but also realize a resistance at the surface of the negative electrode that can reduce the flow of current when an internal short circuit occurs in the secondary battery.

[0055] Meanwhile, the negative electrode mixture layer may include a binder to realize adhesion with the negative electrode current collector and to bind the negative electrode active material, conductive material, and other additives to each other. Examples of such binders include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated-EPDM, styrene butadiene rubber (SBR), fluororubber, and various copolymers thereof, and one or more of these may be used alone or in combination. The binder may be included in an amount of 1 to 10 wt % based on the weight of the negative electrode mixture layer, specifically, 2 to 8 wt % or 1 to 5 wt %.

[0056] The negative electrode may include a negative electrode current collector having high conductivity without inducing chemical changes in the battery. For example, copper, stainless steel, nickel, titanium, calcined carbon, etc. may be used as the negative electrode current collector, and in the case of copper or stainless steel, it is also possible to use a current collector that has been surface-treated with carbon, nickel, titanium, silver, etc. In addition, the negative electrode current collector may have fine irregularities on its surface, similar to the positive electrode current collector, to strengthen the binding force with the negative electrode active material, and may be in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc. In addition, the average thickness of the negative electrode current collector may be preferably 3 to 500 μm, taking into consideration the conductivity and total thickness of the negative electrode to be manufactured.

[0057] <Lithium secondary battery> In one embodiment, the present invention further comprises: There is provided a lithium secondary battery including the above-described anode according to the present invention, a cathode, and a separator disposed between the anode and the cathode.

[0058] As shown in FIG. 2, the lithium secondary battery according to the present invention includes an electrode assembly including a positive electrode 20, a negative electrode 10 according to the present invention, and a separator 30 disposed between the positive electrode and the negative electrode, and has a structure in which the electrode assembly is inserted into a battery case, and then an electrolyte composition is injected and sealed.

[0059] In this case, since the negative electrode contains a silicon-based material as a negative electrode active material, it has a high energy density. Furthermore, since the outermost shell of the multi-layered negative electrode composite layer is provided with an individual composite layer made of a silicon-based material having a relatively low electrical conductivity, the amount of current generated when an internal short circuit occurs can be reduced, thereby improving the safety of the secondary battery against an internal short circuit.

[0060] If the negative electrode has the same structure as the negative electrode of the present invention described above, a detailed description thereof will be omitted below.

[0061] In addition, the positive electrode includes a positive electrode mixture layer prepared by applying a slurry containing a positive electrode active material onto a positive electrode current collector, drying and pressing the slurry, and the slurry may further selectively include a conductive material, a binder, other additives, and the like, as necessary.

[0062] Here, the positive electrode includes a positive electrode composite layer having a multi-layer structure in which two or more individual composite layers are stacked on a positive electrode current collector. Specifically, referring to Fig. 2, the positive electrode 20 includes m (where m>2) positive electrode composite layers 22 arranged on a positive electrode current collector 21, and the first positive electrode composite layer 221a or the mth positive electrode composite layer 221m may include a first positive electrode active material including a lithium composite metal oxide represented by Chemical Formula 1 and a second positive electrode active material including an iron phosphate compound represented by the following Chemical Formula 2.

[0063] [Chemical formula 1] Li x [Ni y Co z Mn w M 1 v ]O2

[0064] [Chemical formula 2] Lifea M 2 1-a XO4

[0065] In the above Chemical Formula 1 and Chemical Formula 2, M 1 is one or more elements selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B and Mo, x, y, z, w, and v are in the range of 1.0≦x≦1.30, 0.1≦y<1, 0≦z≦1, 0≦w≦1, 0≦v≦0.1, and y+z+w+v=1, M 2 is one or more elements selected from the group consisting of W, Cu, Fe, V, Cr, CO, Ni, Mn, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B and Mo; X is one or more selected from the group consisting of P, Si, S, As and Sb; a is 0≦a≦0.5.

[0066] Specifically, the positive electrode mixture layer has a structure in which m (where m≧2) individual positive electrode mixture layers are stacked on a positive electrode current collector. At this time, the positive electrode mixture layer stacked on the surface in contact with the positive electrode current collector is a first positive electrode mixture layer, and a second positive electrode mixture layer or an mth positive electrode mixture layer is stacked in sequence on the first positive electrode mixture layer, so that m individual positive electrode mixture layers are located on the positive electrode current collector.

[0067] The number of layers in the positive electrode mixture layer is not particularly limited as long as it has a structure of two or more layers (where m≧2), and specifically may be 2 to 10 layers, 2 to 8 layers, 2 to 6 layers, or 2 to 4 layers. By adjusting the number of stacked positive electrode mixture layers within the above range, the present invention can improve the energy density of the electrode while preventing a decrease in the manufacturing efficiency of the positive electrode, and at the same time, can effectively release heat generated during charging and discharging of the battery to the outside.

[0068] In addition, the positive electrode mixture layer is manufactured by applying, drying, and pressing a positive electrode active material-containing slurry capable of reversibly intercalating and deintercalating lithium ions during charging and discharging of the battery, and the positive electrode active material may be different in each layer.

[0069] Specifically, the positive electrode according to the present invention has a configuration in which a positive electrode mixture layer includes a first positive electrode active material including a lithium composite metal oxide represented by the following chemical formula 1, and a positive electrode mixture layer separated from the positive electrode current collector, i.e., a second positive electrode mixture layer or an mth positive electrode mixture layer disposed on the first positive electrode mixture layer, further includes a second positive electrode active material including an iron phosphate compound represented by chemical formula 2.

[0070] [Chemical formula 1] Li x [Ni y Co z Mn w M 1 v ]O2

[0071] [Chemical formula 2] Life a M 2 1-a XO4

[0072] In the above Chemical Formula 1 and Chemical Formula 2, M 1 is one or more elements selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B and Mo, x, y, z, w, and v are in the range of 1.0≦x≦1.30, 0.1≦y<1, 0≦z≦1, 0≦w≦1, 0≦v≦0.1, and y+z+w+v=1, M 2 is one or more elements selected from the group consisting of W, Cu, Fe, V, Cr, CO, Ni, Mn, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B and Mo; X is one or more selected from the group consisting of P, Si, S, As and Sb; a is 0≦a≦0.5.

[0073] The lithium composite metal oxide represented by Chemical Formula 1 is a ternary lithium oxide mainly composed of nickel (Ni), cobalt (Co) and manganese (Mn), and has the advantage of being suitable for medium- to large-sized secondary batteries for power storage in the transportation field such as electric vehicles (EVs) and energy storage systems (ESSs) in terms of performance such as high energy density and output. However, although the capacity of the lithium composite metal oxide increases as the content of nickel (Ni) increases, it has a problem in that it is prone to exothermic reactions due to its low chemical and structural stability, which makes it highly likely to cause fires.

[0074] The exothermic reaction may be induced when a short circuit current flows inside the battery, i.e., when an internal short circuit occurs. Generally, the short circuit current in a battery may occur inside the secondary battery due to the penetration of a needle-like object, or may occur in an electronic device connected to the secondary battery.

[0075] Therefore, the present invention includes a lithium composite metal oxide represented by Chemical Formula 1 in the entire positive electrode mixture layer of a multi-layer structure as a first positive electrode active material, and further includes an iron phosphate compound represented by Chemical Formula 2 in the second positive electrode mixture layer or the m-th positive electrode mixture layer separated from the positive electrode current collector as a second positive electrode active material, so that the first positive electrode active material that generates heat during charging and discharging of the battery can be distributed in a position adjacent to the positive electrode current collector that easily transfers heat to the outside. As a result, the present invention can improve the heat resistance of the positive electrode. In addition, the second positive electrode active material is volumized by releasing the lithium inside at an overcharge voltage of about 4.5V or more. As a result, the conductive path is rapidly cut off inside the positive electrode mixture layer including the second positive electrode active material, and an insulating effect can be realized. In addition, the second positive electrode active material has a relatively low electrical conductivity compared to the first positive electrode active material, and can prevent an increase in the amount of short circuit current on the surface of the positive electrode mixture layer during an internal short circuit, thereby suppressing the generation of short circuit heat. In addition, the second positive electrode active material can increase the rigidity of the positive electrode surface, thereby reducing the risk of internal short circuit caused by external force or penetration by a needle-like object.

[0076] In this case, the first positive electrode active material including the lithium composite metal oxide represented by the above Chemical Formula 1 is a metal oxide including nickel (Ni), cobalt (Co) and manganese (Mn) together with lithium, and may include other transition metals (M 1 In a specific example, more specifically, the lithium composite metal oxide may have a doped form of Li(Ni 0.6 Co 0.2 Mn 0.2 )O2, Li(Ni 0.7 Co 0.15 Mn 0.15 )O2, Li(Ni 0.8 Co 0.1 Mn 0.1 )O2, Li(Ni 0.9 Co 0.05 Mn 0.05 )O2, Li(Ni 0.6 Co 0.2 Mn 0.1 Zr 0.1 )O2, Li(Ni 0.6 Co 0.2 Mn 0.15 Zr 0.05)O2 and Li(Ni 0.7 Co 0.1 Mn 0.1 Zr 0.1 ) O2.

[0077] The particle size of the first positive electrode active material is not particularly limited, but may specifically have an average particle size of 0.5 to 5 μm, more specifically, 0.8 to 1.5 μm, 1.0 to 3.0 μm, 1.2 to 1.8 μm, or 1.5 to 2.5 μm.

[0078] In addition, the iron phosphate compound represented by the above formula 2 is a lithium phosphate oxide containing iron, and in some cases, other transition metals (M 2 For example, the iron phosphate compound may have a doped form of LiFePO4, LiFe 0.8 Mn 0.2 PO4, LiFe 0.5 Mn 0.5 It may include PO4, etc.

[0079] The second positive electrode active material containing the iron phosphate compound may have an average particle size of 0.5 to 5 μm, specifically, 0.5 to 1.0 μm, 0.8 to 1.2 μm, 1.0 to 2.0 μm, 1.5 to 3.0 μm, 2.0 to 3.0 μm, or 2.5 to 4.0 μm.

[0080] In addition, the second positive electrode active material may show a tendency that the average particle size of the second positive electrode active material included in each positive electrode mixture layer increases as the position of the individual positive electrode mixture layer changes from the second positive electrode mixture layer to the mth positive electrode mixture layer.

[0081] Specifically, the second positive electrode active material contained in the second positive electrode composite layer may have an average particle size of 0.5 to 1.2 μm, and the second positive electrode active material contained in the mth positive electrode composite layer (where m≧2) may have an average particle size of 1.3 to 3.0 μm.

[0082] As one example, the second positive electrode active material included in the second positive electrode mixture layer may have an average particle size of 0.8 to 1.0 μm, and the second positive electrode active material included in the third positive electrode mixture layer may have an average particle size of 1.2 to 1.5 μm.

[0083] As another example, the second positive electrode active material included in the second positive electrode mixture layer may have an average particle size of 0.6 to 0.8 μm, the second positive electrode active material included in the third positive electrode mixture layer may have an average particle size of 1.5 to 1.8 μm, and the second positive electrode active material included in the fourth positive electrode mixture layer may have an average particle size of 2.0 to 2.2 μm.

[0084] In the positive electrode of the present invention, the average particle size of the second positive electrode active material increases as the position of the individual positive electrode mixture layer changes from the second positive electrode mixture layer to the mth positive electrode mixture layer, thereby making it possible to further increase the rigidity of the positive electrode surface.

[0085] In addition, the second positive electrode active material may be included in an amount of less than 10 wt % based on the weight of the entire positive electrode mixture layer, specifically, 0.1 to 9.9 wt %, 0.5 to 8.0 wt %, 0.5 to 6.0 wt %, 0.1 to 5.0 wt %, 0.1 to 3.0 wt %, 1.0 to 3.0 wt %, 2.5 to 5.0 wt %, 4.0 to 8.0 wt %, or 6.0 to 9.9 wt % based on the weight of the entire positive electrode mixture layer.

[0086] In addition, the second positive electrode active material containing the iron phosphate compound represented by Chemical Formula 2 above may be included in the individual positive electrode mixture layers at 0.5 to 20 wt % relative to the weight of each positive electrode mixture layer, specifically, at 1 to 18 wt %, 1 to 15 wt %, 1 to 12 wt %, 1 to 10 wt %, 1 to 8 wt %, 1 to 5 wt %, 0.5 to 1 wt %, 0.5 to 5 wt %, 2 to 6 wt %, 0.5 to 0.9 wt %, 5 to 16 wt %, 7 to 15 wt %, or 8 to 12 wt % relative to the weight of each positive electrode mixture layer.

[0087] By controlling the content of the second positive electrode active material within the above range relative to the weight of the entire positive electrode composite layer and the individual positive electrode composite layer, the present invention can prevent a situation in which a small content causes insufficient rigidity to be realized on the positive electrode surface, while preventing a deterioration in electrical performance of the battery due to an increase in electrode resistance on the positive electrode surface caused by an excessive amount of the second positive electrode active material.

[0088] Furthermore, the second positive electrode active material may have a tendency that the content in the individual positive electrode composite layer, or the ratio of the content to the weight of the individual positive electrode composite layer, increases as the position of the second positive electrode active material changes from the second positive electrode composite layer adjacent to the first positive electrode composite layer to the mth positive electrode composite layer that is furthest from the first positive electrode composite layer.

[0089] In the case of the second positive electrode active material, the redox reaction proceeds relatively slower compared to the first positive electrode active material when the battery overheats or a short circuit occurs. Therefore, by increasing the concentration closer to the outermost surface of the positive electrode mixture layer, there is an advantage in that the possibility of fire or explosion in the event of an internal short circuit in the battery is reduced.

[0090] Meanwhile, the positive electrode for a lithium secondary battery according to the present invention may further contain a conductive material, a binder, other additives, and the like in the positive electrode mixture layer, if necessary.

[0091] In this case, the first positive electrode active material and the second positive electrode active material contained in each positive electrode mixture layer may be contained in an amount of 85% by weight or more based on the total weight of each positive electrode mixture layer, specifically 90% by weight or more, 93% by weight or more, or 95% by weight or more.

[0092] In addition, the conductive material is used to improve the electrical performance of the positive electrode, and may be any conductive material commonly used in the art. Specifically, the conductive material may include at least one selected from the group consisting of natural graphite, artificial graphite, carbon black, acetylene black, denka black, ketjen black, super P, channel black, furnace black, lamp black, summer black, graphene, and carbon nanotubes.

[0093] The conductive material may be contained in an amount of 0.1 to 5% by weight, based on the total weight of each positive electrode mixture layer, and more specifically, 0.1 to 4% by weight, 2 to 4% by weight, 1.5 to 5% by weight, 1 to 3% by weight, 0.1 to 2% by weight, or 0.1 to 1% by weight.

[0094] In addition, the binder plays a role of binding the positive electrode active material, the positive electrode additive, and the conductive material to each other, and may be used without any particular limitation as long as it has such a function. Specifically, the binder may include one or more resins selected from the group consisting of polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride (PVDF), polyacrylonitrile, polymethylmethacrylate, and copolymers thereof. As an example, the binder may include polyvinylidene fluoride.

[0095] The binder may be contained in an amount of 1 to 10% by weight, specifically 2 to 8% by weight, or 1 to 5% by weight, based on the total weight of each positive electrode mixture layer.

[0096] Furthermore, the total thickness of the positive electrode composite layer is not particularly limited, but may be specifically 50 μm to 300 μm, more specifically 100 μm to 200 μm, 80 μm to 150 μm, 120 μm to 170 μm, 150 μm to 300 μm, 200 μm to 300 μm, or 150 μm to 190 μm.

[0097] In addition, the thickness of the first positive electrode mixture layer in contact with the positive electrode current collector among the individual positive electrode mixture layers constituting the positive electrode mixture layer may be adjusted to a certain range. Specifically, the thickness of the first positive electrode mixture layer may be 10% to 60% of the total thickness of the positive electrode mixture layer, more specifically, 10% to 40%, 30% to 50%, 10% to 20%, or 40% to 60% of the total thickness of the positive electrode mixture layer.

[0098] By adjusting the total thickness and individual thicknesses of the positive electrode mixture layers to the above ranges, the present invention can not only prevent a reduction in the energy density of the electrode, but also realize high adhesive strength between the positive electrode current collector and the positive electrode mixture layers.

[0099] Furthermore, the positive electrode current collector provided in the positive electrode may be one having high conductivity without inducing chemical changes in the battery, such as stainless steel, aluminum, nickel, titanium, calcined carbon, etc., and in the case of aluminum or stainless steel, it may be surface-treated with carbon, nickel, titanium, silver, etc.

[0100] The average thickness of the current collector is preferably 5 to 500 μm, taking into consideration the electrical conductivity and total thickness of the positive electrode to be produced.

[0101] Meanwhile, the separator is interposed between the positive electrode and the negative electrode, and is an insulating thin film having high ion permeability and mechanical strength. The separator is not particularly limited as long as it is a commonly used one in the art, and specifically, a sheet or nonwoven fabric made of chemically resistant and hydrophobic polypropylene, glass fiber, or polyethylene may be used, and in some cases, a composite separator in which inorganic particles / organic particles are coated with an organic binder polymer on a porous polymer substrate such as the sheet or nonwoven fabric may be used. When a solid electrolyte such as a polymer is used as the electrolyte, the solid electrolyte may also serve as the separator. In addition, the pore diameter of the separator may be an average of 0.01 to 10 μm, and the thickness may be an average of 5 to 300 μm.

[0102] In addition, examples of the electrolyte composition include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel-type polymer electrolytes, solid inorganic electrolytes, and molten inorganic electrolytes that can be used in the production of lithium secondary batteries, but are not limited to these.

[0103] Specifically, the electrolyte may include an organic solvent and a lithium salt.

[0104] The organic solvent may be used without any particular limitation as long as it can serve as a medium through which ions involved in the electrochemical reaction of the battery can move. For example, the organic solvent may be an ester solvent such as methyl acetate, ethyl acetate, γ-butyrolactone, or ε-caprolactone, an ether solvent such as dibutyl ether or tetrahydrofuran, a ketone solvent such as cyclohexanone, an aromatic hydrocarbon solvent such as benzene or fluorobenzene, dimethylcarbonate (DMC), diethylcarbonate (DEC), methylethylcarbonate (MEC), ethylmethylcarbonate (EMC), ethylene carbonate (EC), or propylene carbonate (propylene carbonate). Examples of the solvents that can be used include carbonate-based solvents such as ethylene carbonate (PC), alcohol-based solvents such as ethyl alcohol and isopropyl alcohol, nitriles such as R-CN (R is a C2-C20 straight-chain, branched or cyclic hydrocarbon group, which may contain a double bond aromatic ring or an ether bond), amides such as dimethylformamide, dioxolanes such as 1,3-dioxolane, and sulfolanes. Among these, carbonate-based solvents are preferred, and a mixture of a cyclic carbonate (e.g., ethylene carbonate or propylene carbonate) having high ionic conductivity and high dielectric constant that can enhance the charge / discharge performance of a battery and a low-viscosity linear carbonate compound (e.g., ethyl methyl carbonate, dimethyl carbonate or diethyl carbonate) is more preferred. In this case, the cyclic carbonate and the chain carbonate are mixed in a volume ratio of about 1:1 to 9 to produce an excellent electrolyte performance.

[0105] The lithium salt may be used without any particular limitation as long as it is a compound capable of providing lithium ions used in a lithium secondary battery. Specifically, the lithium salt may be LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI, or LiB(C2O4)2.

[0106] The lithium salt may be used at a concentration within the range of 0.1 M to 2.0 M. When the lithium salt concentration is within the above range, the electrolyte has suitable conductivity and viscosity, and therefore can exhibit excellent electrolyte performance and can effectively migrate lithium ions.

[0107] In addition to the electrolyte components, the electrolyte may further contain one or more additives such as haloalkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinoneimine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, or aluminum trichloride, for the purpose of improving the life characteristics of the battery, suppressing the decrease in the capacity of the battery, improving the discharge capacity of the battery, etc. In this case, the additives may be contained in an amount of 0.1% by weight to 5% by weight based on the total weight of the electrolyte.

[0108] As described above, the positive electrode active material composition according to the present invention or a lithium secondary battery including a positive electrode prepared using the same stably exhibits excellent discharge capacity, output characteristics, and capacity retention rate, and is therefore useful in portable devices such as mobile phones, notebook computers, and digital cameras, and in the field of electric vehicles such as hybrid electric vehicles (HEVs), etc.

[0109] Furthermore, the lithium secondary battery according to the present invention is not limited in shape depending on the application of the battery, and may be in the form of a case commonly used in the art. For example, the lithium secondary battery may be a battery including a cylindrical or square battery case using a can, or a pouch or coin battery case.

[0110] As one example, the lithium secondary battery may be a prismatic secondary battery including a prismatic can as a battery case.

[0111] <Secondary battery module> Furthermore, in one embodiment, the present invention provides a secondary battery module including the above-described lithium secondary battery according to the present invention.

[0112] The secondary battery module according to the present invention includes the above-described lithium secondary battery of the present invention as a unit battery, and has excellent electrical performance as well as excellent safety against internal short circuits, and can be used as a power source for medium to large devices that require high temperature stability, long cycle characteristics, high rate characteristics, etc.

[0113] Specific examples of such medium- to large-sized devices include power tools that are powered by battery-type motors, electric vehicles including electric vehicles (EVs), hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (PHEVs), electric bicycles (E-bikes), electric two-wheeled vehicles including electric scooters (E-scooters), electric golf carts, power storage systems, etc. More specifically, hybrid electric vehicles (HEVs) are included, but are not limited thereto.

[0114] The present invention will now be described in more detail with reference to examples and experimental examples.

[0115] However, the following examples and experimental examples are merely illustrative of the present invention, and the content of the present invention is not limited to the following examples and experimental examples.

[0116] <Examples 1 to 10 and Comparative Examples 1 to 4. Production of Lithium Secondary Batteries> A) Manufacturing of negative electrodes Water was poured into a homo mixer, and a carbon-based material in which natural graphite and artificial graphite were mixed in a weight ratio of 1:1 as the first negative electrode active material, and SiO q (where 0.9≦q≦2.2), and styrene butadiene rubber (SBR) were then added. After that, mixing was performed for 80 minutes at 2500 rpm to prepare a first negative electrode composite layer forming slurry, a second negative electrode composite layer forming slurry, and a third negative electrode composite layer forming slurry.

[0117] The slurry for forming each negative electrode composite layer was prepared to contain 98.5% by weight of the negative electrode active material and 1.5% by weight of the binder based on the solid content. q ) the sphericity and (2) the content ratio (unit: parts by weight) of the first negative electrode active material and the second negative electrode active material contained in each slurry relative to 150 parts by weight of the total negative electrode active material were adjusted as shown in Table 1.

[0118] A copper sheet (average thickness: 12 μm) was prepared as a negative electrode current collector, and the previously prepared slurries for forming the first to third negative electrode composite layers were sequentially cast onto the prepared copper sheet. The copper sheet onto which the slurries were cast was dried in a vacuum oven at 130° C. and then rolled to prepare a negative electrode. At this time, the total thickness of the rolled negative electrode composite layers was 140 μm, and the thicknesses of the individual negative electrode composite layers were adjusted to be the same.

[0119] [Table 1]

[0120] b) Manufacturing of positive electrodes Pour N-methylpyrrolidone solvent into a homo mixer and add LiNi 0.8 Co 0.1 Mn 0.1 The first positive electrode active material was LiFePO4 (hereinafter referred to as "LFP"), the second positive electrode active material was carbon black, and the binder was polyvinylidene fluoride (PVDF). The mixture was then mixed at 3,000 rpm for 60 minutes to prepare a first positive electrode composite layer forming slurry, a second positive electrode composite layer forming slurry, and a third positive electrode composite layer forming slurry.

[0121] The slurry prepared for forming each positive electrode composite layer contained 97% by weight of the positive electrode active material, 2% by weight of the conductive material, and 1% by weight of the binder based on the solid content. In addition, (1) the average particle size (unit: μm) of the second positive electrode active material and (2) the content ratio (unit: parts by weight) of the first to third positive electrode active materials contained in each slurry relative to 150 parts by weight of the total positive electrode active material were adjusted as shown in Table 2.

[0122] An aluminum thin plate (average thickness: 14 μm) was prepared as a positive electrode current collector, and the previously prepared first positive electrode composite layer forming slurry to third positive electrode composite layer forming slurry were sequentially cast onto the prepared aluminum thin plate, dried in a vacuum oven at 130° C., and rolled to prepare a positive electrode. At this time, the total thickness of the rolled positive electrode composite layer was 150 μm, and the thickness of each individual positive electrode composite layer was adjusted to be the same.

[0123] [Table 2]

[0124] C) Assembly of secondary batteries As shown in Table 3 below, the positive and negative electrodes prepared in advance were placed opposite each other, and an 18 μm polypropylene separator was placed between them to fabricate an electrode assembly. Each electrode assembly prepared was inserted into a rectangular battery case, and an electrolyte composition was injected into the battery case, and the case was sealed to fabricate a rectangular lithium secondary battery. At this time, a solution in which lithium hexafluorophosphate (LiPF6, 1.0M) and vinyl carbonate (VC, 2 wt%) were mixed into a mixture of ethylene carbonate (EC): dimethyl carbonate (DMC): diethyl carbonate (DEC) = 1: 1: 1 (volume ratio) was used as the electrolyte composition.

[0125] [Table 3]

[0126] <Experimental Example> In order to evaluate the performance and safety of the lithium secondary battery according to the present invention, the following experiments were carried out.

[0127] a) Evaluation of secondary battery output The lithium secondary batteries manufactured in each of the examples and comparative examples were fully charged at 0.1 C-rate at room temperature (22°C). The fully charged lithium secondary batteries were then discharged at 0.1 C-rate to measure the initial discharge capacity. The lithium secondary batteries were then fully charged at 0.1 C-rate again, and discharged at 1.0 C, 2.0 C, 5.0 C, and 9.0 C-rates to measure the relative discharge capacity based on the initial discharge capacity for each discharge rate. The results are shown in Table 4 below.

[0128] b) Evaluation of nail penetration test For the lithium secondary batteries manufactured in each of the examples and comparative examples, a charge / discharge cycle was repeated twice at a current value of 0.5 C in a voltage range of 4.2 to 2.0 V in an environment of 25° C. Then, each lithium secondary battery was charged to 4.2 V, and then a metal object with a diameter of 3 mm was lowered at a speed of 80 mm / sec to penetrate the cell in the same manner as the PV8450 certification conditions, and the presence or absence of ignition was evaluated. The results are shown in Table 5.

[0129] C) Evaluation of impact test The lithium secondary batteries manufactured in each of the examples and comparative examples were fully charged at room temperature (22°C) at 0.1C-rate. Then, a secondary battery impact test was conducted on the fully charged lithium secondary batteries in accordance with the UN1642DL impact certification standard. The weight used was 9 kg, and the experiment was conducted by dropping it onto a round bar with a diameter of 16 mm placed on the secondary battery cell. The results are shown in Table 5 below.

[0130] [Table 4]

[0131] [Table 5]

[0132] As shown in Tables 4 and 5, it is apparent that the positive electrode for a lithium secondary battery according to the present invention not only has a high energy density, but also has an excellent effect of improving the safety of the battery.

[0133] Specifically, it was shown that the secondary battery of the embodiment according to the present invention maintained a discharge capacity ratio of 89% or more even during high-rate discharge of 5.0 C-rate or more, which means that the output of the lithium secondary battery including the positive electrode of the embodiment is excellent.

[0134] It was also confirmed that the secondary batteries of the examples did not ignite during the nail penetration test and impact test, which means that the secondary batteries according to the present invention are highly safe.

[0135] From these results, it can be seen that the lithium secondary battery according to the present invention contains a ternary compound containing nickel (Ni), cobalt (Co), manganese (Mn) and the like, and at the same time, small amounts of silicon-based oxide and iron phosphate compound are contained in the outermost shell of the composite layer adjacent to the separator in the positive electrode and negative electrode, respectively, thereby not only providing excellent battery energy density, but also relatively low electrical conductivity on the positive electrode surface and negative electrode surface, thereby improving safety in the event of an internal short circuit in the secondary battery.

[0136] Although the present invention has been described above with reference to preferred embodiments, it will be understood that a person skilled in the art or having ordinary knowledge in the art may make various modifications and changes to the present invention without departing from the spirit and technical scope of the present invention as described in the claims below.

[0137] Therefore, the technical scope of the present invention should not be limited to the contents described in the Summary of the Invention of the specification, but should be defined by the claims. [Explanation of symbols]

[0138] 1: Lithium secondary battery 10:Negative electrode 11: Negative electrode current collector 12: Multi-layered negative electrode composite layer 121: Individual negative electrode composite layer 121a: First negative electrode composite layer 121n: nth negative electrode composite layer 20: Positive electrode 21: Positive electrode current collector 22: Multi-layered positive electrode composite layer 221: Individual positive electrode composite layer 221a: First positive electrode composite layer 221m: mth positive electrode composite layer

Claims

1. a first negative electrode mixture layer or an nth negative electrode mixture layer (n≧2) is disposed on a negative electrode current collector; the first negative electrode mixture layer or the (n-1)th negative electrode mixture layer includes a first negative electrode active material including a carbon-based material and a second negative electrode active material including a silicon-based material; The nth negative electrode mixture layer includes a second negative electrode active material containing a silicon-based material.

2. 2. The negative electrode for a lithium secondary battery according to claim 1, wherein the first negative electrode composite layer or the n-1th negative electrode composite layer has an increasing content or a content ratio of the second negative electrode active material as the position of the individual negative electrode composite layer changes from the first negative electrode composite layer to the n-1th negative electrode composite layer.

3. 2. The negative electrode for a lithium secondary battery according to claim 1, wherein the carbon-based material comprises at least one selected from the group consisting of soft carbon, hard carbon, natural graphite, artificial graphite, expanded graphite, non-graphitizable carbon, carbon black, acetylene black, ketjen black, carbon nanotubes, fullerene, activated carbon, graphene, and carbon fiber.

4. The silicon-based materials include silicon (Si), silicon carbide (SiC) and silicon oxide (SiO q 2. The negative electrode for a lithium secondary battery according to claim 1, comprising at least one of the following:

5. The negative electrode of claim 1 , wherein the second negative electrode active material is contained in an amount of 1 wt % to 20 wt % based on a total weight of the negative electrode active material.

6. 2. The negative electrode for a lithium secondary battery according to claim 1, wherein the second negative electrode active material has a spheroidization degree of 0.5 to 1.0, and the spheroidization degree decreases as the position of the individual negative electrode mixture layer changes from the first negative electrode mixture layer to the nth negative electrode mixture layer.

7. 2. The negative electrode for a lithium secondary battery according to claim 1, wherein the total thickness of the negative electrode mixture layer is 50 μm or more and 300 μm or less.

8. 2 . The negative electrode for a lithium secondary battery according to claim 1 , wherein a thickness of the nth negative electrode mixture layer is 5% to 30% of a total thickness of the positive electrode mixture layers.

9. A lithium secondary battery comprising the negative electrode according to any one of claims 1 to 8, a positive electrode, and a separator located between the negative electrode and the positive electrode.

10. The positive electrode has a first positive electrode mixture layer or an mth positive electrode mixture layer (where m≧2) disposed on a positive electrode current collector, The first positive electrode mixture layer or the mth positive electrode mixture layer includes a first positive electrode active material including a lithium composite metal oxide represented by Chemical Formula 1, and a second positive electrode active material including an iron phosphate compound represented by the following Chemical Formula 2, [Chemical formula 1] Li x [Ni y Co z Mn w M 1 v ]O 2 [Chemical formula 2] LiFe a M 2 1-a XO 4 In the above Chemical Formula 1 and Chemical Formula 2, M 1 is one or more elements selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B and Mo; x, y, z, w and v are each in the range of 1.0≦x≦1.30, 0.1≦y<1, 0≦z≦1, 0≦w≦1, 0≦v≦0.1, and y+z+w+v=1; M 2 is one or more elements selected from the group consisting of W, Cu, Fe, V, Cr, CO, Ni, Mn, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo; X is at least one selected from the group consisting of P, Si, S, As and Sb; 10. The lithium secondary battery according to claim 9, wherein a satisfies 0≦a≦0.

5.

11. 11. The lithium secondary battery of claim 10, wherein the content or the ratio of the content of the second positive electrode active material in each positive electrode mixture layer increases as the position of the individual positive electrode mixture layer changes from the first positive electrode mixture layer to the mth positive electrode mixture layer.

12. The lithium secondary battery according to claim 10 , wherein the second positive electrode active material is contained in an amount of less than 10 wt % based on the total weight of the positive electrode mixture layer.

13. The lithium secondary battery according to claim 10 , wherein the total thickness of the positive electrode mixture layer is 50 μm or more and 300 μm or less.

14. A secondary battery module comprising the lithium secondary battery according to claim 9.

Citation Information

Patent Citations

  • Negative electrode plate, electrochemical device, and electronic device

    EP3886218A1

  • Nonaqueous electrolyte secondary battery

    JP2015046220A

  • Nonaqueous electrolyte secondary battery

    JP2016058187A

  • Nonaqueous electrolyte secondary battery

    JP2016058309A

  • Negative electrode for nonaqueous electrolyte secondary battery, and nonaqueous electrolyte secondary battery arranged by use thereof

    JP2018063920A